Penerapan Teknologi Pengendalian Penyakit Tanaman Yang Ramah Lingkungan Pada Tembakau - Mugiastuti, Endang; Soesanto, Loekas; Manan, Abdul (JPPM (Jurnal Pengabdian dan Pemberdayaan Masyarakat), 2018)
Tobacco is one of the most important plants which were cultivated by Farmers Groups "Darma Mukti Tani I" and "Karya Tani" of Wangon District, Banyumas Regency. However, several obstacles often interfere with the production of tobacco, including quite high tobacco pests and diseases. Socialization ofÂ  plant pests diseases management by using Trichoderma sp. and Pseudomonas fluorescens biopesticides, needs to be done. The activity aimed was to increase knowledge and skills of farmers on pests and diseases in tobacco and their management measures with biological pesticides. Issues addressed farmers partners with several technology solution, which was conducted by the transfer of technology through education, training, demonstration plots, and mentoring. Dissemination activities were able to increase their knowledge of pests and diseases, their control, and the control of environmental friendly as 58,82, 62,5, and 67.67%, respectively. The training activities of P. fluorescens exploration was able to improve their ability as 166.67%. Propagation activity and application training could improve their ability for 100 and 73,33%, respectively. The training activities of Trichoderma sp. exploration were able to improve their ability as 94,44%, while the propagation and application training could improve their ability, respectively, as 73,33 and 88.23%. Application of biological pesticides P. fluorescens and Trichoderma sp. at demonstration plot was able to increase growth and reduced the intensity of bacterial and fusarium wilt disease by 40-50%. Keywords: Tobacco, technology transfer, pests and diseases, biological control.